“(IM)MOBILE PRECARITY” AMONG YOUNG PEOPLE IN NEWFOUNDLAND AND LABRADOR - Power, Nicole (International Journal of Child, Youth and Family Studies, 2021)
Mobility for work and education among young people has been a key feature of contemporary life. Drawing on focus groups with youth living in the Canadian province of Newfoundland and Labrador, as well as key informant interviews with people who work for community-based organizations that serve youth, I examine the relationship between young people’s employment- and education-related geographical mobilities and precarity. I draw on recent insights from scholars examining precarity as grounded in both labouring conditions and ontological experience. In foregrounding the experiences and subjectivities of poor and working-class youth, I show how the structure of youth labour markets and of education and training cheapens youth labour, with implications for youth’s capacity for independence. In a context of broader regimes of mobility associated with resource extraction, young people without formal qualifications live precarious lives: they move from job to job and place to place, and rely on family and friends to support their housing and other needs. In this context of uncertainty and labour market volatility, youth expressed disorientation regarding decisions about work, education, and mobility, reflecting the high stakes of not making the “right” choice, and developed a pragmatic approach to work as a way to make a living rather than a pathway to a meaningful life. I conclude by situating these findings as a critique not just of precarity but of capitalist economic arrangements more broadly, with implications for the kinds of solutions that can address structural class inequalities.